A Frustrated Lewis Pair Based on a Cationic Aluminum Complex and Triphenylphosphine - Stennett, Thomas; Pahl, Jürgen; Zijlstra, Harmen; Seidel, Falk W.; Harder, Sjoerd (Organometallics, 2016)
The highly Lewis acidic, cationic aluminum species [DIPP-nacnacAlMe](+)[B(C6F5)(4)](-) (1, DIPP-nacnac = [HCC(Me)N(2,6-(Pr2C6H3)-Pr-i)(2)](-)) has been shown to undergo reactions with a wide variety of small molecules, in both the presence and absence of an external weak phosphine base, PPh3. Cycloaddition reactions of unsaturated C C bonds across the aluminum diketiminate framework are reported, and the first structural confirmation of this type of cycloaddition product is presented. Addition of PPh3 to 1 produces the cationic aluminum phosphine complex [DIPP-nacnacAl(Me)PPh3](+)[B(C6F5)(4)](-), which undergoes fluxional dissociation/coordination of the phosphine in solution. This weak Al-P interaction can be utilized in frustrated Lewis pair type reactions to activate alkenes, alkynes, CO2, propylene oxide, and the C-Cl bonds of CH2Cl2. The CO2 adduct [DIPP-nacnacAl(Me)OC-(PPh3)O](+)[B(C6F3)(4)](-) undergoes further stoichiometric reduction with Et3SiH to produce an aluminum formate species.

An unsymmetrical phosphonium diylide with a fluorenylidene subunit and its lithium complexes - Geitner, Robert; Kosygin, Irina; Görls, Helmar; Pahl, Jürgen; Harder, Sjoerd; Westerhausen, Matthias; Langer, Jens (Journal of Coordination Chemistry, 2015)
The phosphonium ylide MePh2P(flu) (3) (flu = C13H8, fluorenylidene) was conveniently prepared by reaction of Ph2P(fluH) (1) (fluH = C13H9, fluorenyl) with iodomethane, followed by subsequent dehydrohalogenation of the resulting phosphonium salt [MePh2P(fluH)] I (2) by potassium tert-butoxide. Compound 3 was further deprotonated by n-butyllithium, yielding the corresponding lithium complex [LiCH2PPh2(flu)(tmeda)] (4) in presence of N,N,N',N'-tetramethylethylenediamine (tmeda). This mononuclear lithium compound contains the monoanionic chelating diylidic ligand. An exchange of the neutral bidentate tmeda by tridentate N,N,N',N'',N''-pentamethyldiethylenetriamine (pmdta) enforces a change in coordination mode. Consequently, the diylide is monodentate in [LiCH2PPh2(flu)(pmdta)] (5). Compounds 1-5 were characterized by NMR spectroscopy and single-crystal X-ray diffraction experiments.
Keywords: Lithium; Phosphonium halides; Phosphonium ylides; Diylides; Phosphanes; Fluorenylidene; X-ray crystallography

Bulky cationic β-diketiminate magnesium complexes - Friedrich, Alexander; Pahl, Jürgen; Elsen, Holger; Harder, Sjoerd (Dalton Transactions, 2019)
Cationic β-diketiminate Mg complexes with the bulky tBu BDI ligand and the weakly coordinating anion B(C 6 F 5 ) 4 - have been prepared by the reaction of ( tBu BDI)MgnBu with [Ph 3 C] + [B(C 6 F 5 ) 4 ] - ; tBu BDI = CH[C(tBu)N-Dipp] 2 and Dipp = 2,6-diisopropylphenyl. Their structures are compared to the previously reported cationic ( Me BDI)Mg + complexes; Me BDI = CH[C(Me)N-Dipp] 2 . Crystallization of [( tBu BDI)Mg] + [B(C 6 F 5 ) 4 ] - from chlorobenzene gave a unique ( tBu BDI)Mg + ·ClC 6 H 5 cation with a rather short Mg⋯Cl and consequently long C-Cl bond. Crystallization from chlorobenzene/arene solvent mixtures gave ( tBu BDI)Mg + ·arene complexes (arene = benzene, toluene, m-xylene) but in the presence of mesitylene the chlorobenzene complex was formed. Due to the greater shielding of the metal, none of these complexes display Mg⋯(F 5 C 6 ) 4 B - interactions. Crystal structures of the arene complexes show in all cases η 2 -coordination of the arene ligands. Ring slippage from a more favorable η 2 -coordination can be explained by the steric bulk of the tBu BDI ligand. The smaller arenes, benzene and toluene, also bind to ( tBu BDI)Mg + in bromobenzene solution. The Lewis acidity of these cationic Mg complexes was determined by the Gutmann-Beckett test. The acceptor number for ( tBu BDI)Mg + (AN = 76.0) is substantially higher than that estimated for ( Me BDI)Mg + (AN = 70.3). Calculation of the atomic NPA charges by DFT shows that the Mg 2+ ion in ( tBu BDI)Mg + is slightly more positively charged than the metal in ( Me BDI)Mg + , confirming its higher Lewis acidity. The lower benzene complexation energy calculated for ( tBu BDI)Mg + versus ( Me BDI)Mg + is due to steric congestion of the metal in the ( tBu BDI)Mg + cation which allows only for Mg⋯(η 1 )C 6 H 6 instead of Mg⋯(η 6 )C 6 H 6 bonding. This ring slippage, however, results in a significant polarization of the electron density in the benzene ring, making it susceptible for nucleophilic attack..
CRIS-Team Scopus Importer:2019-05-09

Calcium Hydride Catalyzed Highly 1,2-Selective Pyridine Hydrosilylation - Intemann, Julia; Bauer, Heiko; Pahl, Jürgen; Maron, Laurent; Harder, Sjoerd (Chemistry - A European Journal, 2015)
Reaction of the calcium hydride complex (DIPPnacnac-CaHTHF)(2) with pyridine is much faster and selective than that of the corresponding magnesium hydride complex (DIPPnacnac = [(2,6-iPr(2)C(6)H(3))NC(Me)](2)CH). With a range of pyridine, picoline and quinoline substrates, exclusive transfer of the hydride ligand to the 2-position is observed and also at higher temperatures no 1,21,4 isomerization is found. The heteroleptic product DIPPnacnac-Ca(1,2-dihydropyridide)(pyridine) shows fast ligand exchange into homoleptic calcium complexes and therefore could not be isolated. Calcium hydride reduction of isoquinoline gave well-defined homoleptic products which could be characterized by X-ray diffraction: Ca(1,2-dihydroisoquinolide)(2)(isoquinoline)(4) and Ca-3(1,2-dihydroisoquinolide)(6)(isoquinoline)(6). The striking selectivity difference in the dearomatization of pyridines by Mg or Ca complexes could be explained by DFT theory and was utilized in catalysis. Whereas hydroboration of pyridine with pinacol borane with a calcium hydride catalyst gave only minor conversion, the hydrosilylation of pyridine and quinolines with PhSiH3 yields exclusively 1,2-dihydropyridine and 1,2-dihydroquinoline silanes with 80-90% conversion. Similar results can be achieved with the catalyst Ca[N(SiMe3)(2)](2)(THF)(2). These calcium complexes represent the first catalysts for the 1,2-selective hydrosilylation of pyridines.
Keywords: calcium; catalysis; hydride; hydrosilylation; reduction

Cationic Aluminium Complexes as Catalysts for Imine Hydrogenation - Friedrich, Alexander; Eyselein, Jonathan; Elsen, Holger; Langer, Jens; Pahl, Jürgen; Wiesinger, Michael; Harder, Sjoerd (Chemistry - A European Journal, 2021)
Strongly Lewis acidic cationic aluminium complexes, stabilized by β–diketiminate (BDI) ligands and free of Lewis bases, have been prepared as their B(C6F5)4− salts and were investigated for catalytic activity in imine hydrogenation. The backbone (R1) and N (R2) substituents on the R1,R2BDI ligand (R1,R2BDI=HC[C(R1)N(R2)]2) influence sterics and Lewis acidity. Ligand bulk increases along the row Me,DIPPBDI<Me,DIPePBDI≈tBu,DIPPBDI<tBu,DIPePBDI; DIPP=2,6-C(H)Me2-phenyl, DIPeP=2,6-C(H)Et2-phenyl. The Gutmann-Beckett test showed acceptor numbers of: (tBu,DIPPBDI)AlMe+ 85.6, (tBu,DIPePBDI)AlMe+ 85.9, (Me,DIPPBDI)AlMe+ 89.7, (Me,DIPePBDI)AlMe+ 90.8, (Me,DIPPBDI)AlH+ 95.3. Steric and electronic factors need to be balanced for catalytic activity in imine hydrogenation. Open, highly Lewis acidic, cations strongly coordinate imine rendering it inactive as a Frustrated Lewis Pair (FLP). The bulkiest cations do not coordinate imine but its combination is also not an active catalyst. The cation (tBu,DIPPBDI)AlMe+ shows the best catalytic activity for various imines and is also an active catalyst for the Tishchenko reaction of benzaldehyde to benzylbenzoate. DFT calculations on the mechanism of imine hydrogenation catalysed by cationic Al complexes reveal two interconnected catalytic cycles operating in concert. Hydrogen is activated either by FLP reactivity of an Al⋅⋅⋅imine couple or, after formation of significant quantities of amine, by reaction with an Al⋅⋅⋅amine couple. The latter autocatalytic Al⋅⋅⋅amine cycle is energetically favoured.
CRIS-Team Scopus Importer:2021-05-07
Keywords: Aluminium; cations; DFT; hydrogenation; imine

Complexation and Versatile Reactivity of a Highly Lewis Acidic Cationic Mg Complex with Alkynes and Phosphines - Pahl, Jürgen; Stennett, Thomas; Volland, Michel; Guldi, Dirk Michael; Harder, Sjoerd (Chemistry - A European Journal, 2019)
[(BDI)Mg+][B(C6F5)(4)(-)] (1; BDI=CH[C(CH3)NDipp](2); Dipp=2,6-diisopropylphenyl) was prepared by reaction of (BDI)MgnPr with [Ph3C+][B(C6F5)(4)(-)]. Addition of 3-hexyne gave [(BDI)Mg+(EtCCEt)][B(C6F5)(4)(-)]. Single-crystal X-ray analysis, NMR investigations, Raman spectra, and DFT calculations indicate a significant Mg-alkyne interaction. Addition of the terminal alkynes PhCCH or Me3SiCCH led to alkyne deprotonation by the BDI ligand to give [(BDI-H)Mg+(CCPh)](2)2[B(C6F5)(4)(-)] (2, 70%) and [(BDI-H)Mg+(CCSiMe3)](2)2[B(C6F5)(4)(-)] (3, 63%). Addition of internal alkynes PhCCPh or PhCCMe led to [4+2] cycloadditions with the BDI ligand to give Mg+C(Ph)=C(Ph)C[C(Me)=NDipp](2)(2) 2[B(C6F5)(4)(-)] (4, 53%) and Mg+C(Ph)=C(Me)C[C(Me)=NDipp](2)(2)2[B(C6F5)(4)(-)] (5, 73%), in which the Mg center is N,N,C-chelated. The (BDI)Mg+ cation can be viewed as an intramolecular frustrated Lewis pair (FLP) with a Lewis acidic site (Mg) and a Lewis (or BrOnsted) basic site (BDI). Reaction of [(BDI)Mg+][B(C6F5)(4)(-)] (1) with a range of phosphines varying in bulk and donor strength generated [(BDI)Mg+PPh3][B(C6F5)(4)(-)] (6), [(BDI)Mg+PCy3][B(C6F5)(4)(-)] (7), and [(BDI)Mg+ PtBu3][B(C6F5)(4)(-)] (8). The bulkier phosphine PMes(3) (Mes=mesityl) did not show any interaction. Combinations of [(BDI)Mg+][B(C6F5)(4)(-)] and phosphines did not result in addition to the triple bond in 3-hexyne, but during the screening process it was discovered that the cationic magnesium complex catalyzes the hydrophosphination of PhCCH with HPPh2, for which an FLP-type mechanism is tentatively proposed.
CRIS-Team WoS Importer:2019-03-01

Heteroleptic Heavier Alkaline Earth Metal Amide Complexes Stabilized by a Superbulky β-Diketiminate Ligand - Gentner, Thomas; Rösch, Bastian; Thum, Katharina; Langer, Jens; Ballmann, Gerd; Pahl, Jürgen; Donaubauer, Wolfgang; Hampel, Frank; Harder, Sjoerd (Organometallics, 2019)
Heteroleptic alkaline earth metal (Ae = Ca, Sr, Ba) amide complexes with the superbulky β-diketiminate ligand DIPePBDI (CH[C(Me)N-DIPeP]2, DIPeP = 2,6-di-iso-pentylphenyl) have been prepared by direct deprotonation of DIPePBDI-H with either AeN′′2 or AeN′′2·(THF)2 (N′′ = N(SiMe3)2). Despite long reaction times of 5-14 days, this convenient one-step synthetic method has the major advantage that metal-pure products are obtained in generally quantitative yields. All (DIPePBDI)AeN′′ and (DIPePBDI)AeN′′·THF complexes are monomeric and stabilized by agostic metal···Me3Si and metal···iso-pentyl interactions. They are highly soluble in toluene and indefinitely stable toward ligand scrambling, even after 2 weeks at 140 °C. The same series with the smaller DIPPBDI ligand (CH[C(Me)N-DIPP]2, DIPP = 2,6-di-iso-propylphenyl) could, except for Ca, also be prepared by direct ligand deprotonation. The (DIPPBDI)CaN′′ and (DIPPBDI)CaN′′·THF complexes are stable toward ligand exchange up to 110 °C. Whereas THF-free (DIPPBDI)SrN′′ and (DIPPBDI)BaN′′ decompose at 50 and 20 °C, respectively, their THF adducts were found to be stable up to 60 °C. This is, however, strongly dependent on complex purity. Slight hydrolysis or contamination with KN′′ accelerates ligand scrambling. Therefore, partial hydrolysis and salt metathesis routes that involve KN′′ should be avoided when synthesizing heteroleptic complexes of the heavier Ae metals.
CRIS-Team Scopus Importer:2019-07-09

Ligand Effects in Calcium Catalyzed Ketone Hydroboration - Brand, Steffen; Causero, Andrea; Elsen, Holger; Pahl, Jürgen; Langer, Jens; Harder, Sjoerd (European Journal of Inorganic Chemistry, 2020)
The first “naked” (Lewis base-free) cationic Ca amidinate complex [tBuAmDIPPCa(C6H6)]+[B(C6F5)4]– was prepared in 62 % yield tBuAmDIPP = tBuC(N–DIPP)2; DIPP = 2,6-diisopropylphenyl by reaction of [tBuAmDIPPCaH]2 with [Ph3C]+[B(C6F5)4]– in chlorobenzene. The ether-free complex tBuAmDIPPCaN(SiMe3)2 was obtained by removal of diethyl ether from its ether adduct. Crystal structures show that the amidinate ligand in both complexes is N,Aryl-chelating. In this coordination mode the bulk of the amidinate ligand is comparable to that of a DIPP-substituted β-diketiminate ligand. Isomers with N,N-coordinating amidinate ligands are circa 15 kcal/mol higher in energy and this coordination mode is only present in case additional ether ligands compensate for energy loss or in case of space limitation at the metal, e.g. in homoleptic (tBuAmDIPP)2Ca. A series of four Ca amidinate complexes, tBuAmDIPPCaX, were tested in the catalytic hydroboration of ketones and aldehydes by pinacolborane (HBpin). Catalytic activities increase for X– = I– < B(C6F5)4 – < (Me3Si)2N– ≈ H–. For catalysts with unreactive anions, like I– or B(C6F5)4 –, catalyst performance increases with the Lewis acidity of the metal and a mechanism is proposed in which HBpin and ketone coordinate to the Ca2+ ion which is followed by direct hydroboration. The more active catalysts with X– = (Me3Si)2N– or H– likely operate through a mechanism which involves intermediate metal hydride (or borate) complexes.
CRIS-Team Scopus Importer:2020-05-08
Keywords: Amidinates; Calcium; Cationic complexes; Homogeneous catalysis; Hydroboration

Magnesium-halobenzene bonding: mapping the halogen sigma-hole with a Lewis-acidic complex - Friedrich, Alexander; Pahl, Jürgen; Eyselein, Jonathan; Langer, Jens; van Eikema Hommes, Nico; Görling, Andreas; Harder, Sjoerd (Chemical Science, 2021)
Complexes of the Lewis base-free cations (MeBDI)Mg+and (tBuBDI)Mg+with Ph-X ligands (X = F, Cl, Br, I) have been studied (MeBDI = HC[C(Me)N-DIPP]2andtBuBDI = HC[C(tBu)N-DIPP]2; DIPP = 2,6-diisopropylphenyl). For the smaller β-diketiminate ligand (MeBDI) only complexes with PhF could be isolated. Heavier Ph-X ligands could not compete with bonding of Mg to the weakly coordinating anion B(C6F5)4−. For the cations with the bulkiertBuBDI ligand, the full series of halobenzene complexes was structurally characterized. Crystal structures show that the Mg⋯X-Ph angle strongly decreases with the size of X: F 139.1°, Cl 101.4°, Br 97.7°, I 95.1°. This trend, which is supported by DFT calculations, can be explained with the σ-hole which increases from F to I. Charge calculation and Atoms-In-Molecules analyses show that Mg⋯F-Ph bonding originates from electrostatic attraction between Mg2+and the very polar Cδ+-Fδ−bond. For the heavier halobenzenes, polarization of the halogen atom becomes increasingly important (Cl < Br < I). Complexation with Mg leads in all cases to significant Ph-X bond activation and elongation. This unusual coordination of halogenated species to early main group metals is therefore relevant to C-X bond breaking.
CRIS-Team Scopus Importer:2021-03-19

Retro-Diels-Alder decomposition of norbornadiene mediated by a cationic magnesium complex - Thum, Katharina; Pahl, Jürgen; Eyselein, Jonathan; Elsen, Holger; Langer, Jens; Harder, Sjoerd (Chemical Communications, 2021)
First evidence for the coordination of norbornadiene (nbd) and dicyclopentadiene (dcpd) with the main group metal Mg is provided by the crystal structures of adducts with cationic beta-diketiminate (BDI) Mg complexes. While the dcpd complex is thermally stable, [(BDI)Mg+center dot nbd][B(C6F5)(4)(-)] shows slow room temperature retro-Diels-Alder decomposition to give a complex with the cation (BDI)Mg(C5H5)Mg(BDI)(+).
CRIS-Team WoS Importer:2021-05-28

s-Block Metal Dibenzoazepinate Complexes: Evidence for Mg-Alkene Encapsulation - Freitag, Benjamin; Elsen, Holger; Pahl, Jürgen; Ballmann, Gerd; Herrera, Alberto Cesar; Dorta, Romano; Harder, Sjoerd (Organometallics, 2017)

Stabilizing Magnesium Hydride Complexes with Neutral Ligands - Wiesinger, Michael; Maitland, Brant; Elsen, Holger; Pahl, Jürgen; Harder, Sjoerd (European Journal of Inorganic Chemistry, 2019)
The reaction of Mg[N(SiMe3)(2)](2) with PhSiH3 in benzene at room temperature gave a white precipitate of approximate constitution MgH1.5N ''(0.5). This undefined hydride rich Mg salt can be dissolved by addition of well-known neutral donors, such as PMDTA, DABCO or the N-heterocyclic carbene I(Me)iPr (N,N '-diisopropyl-2,3-dimethylimidazol-2-ylidine). This allowed for crystallization and structural characterization of five new magnesium hydride complexes: Mg-2(mu-H)(2)N ''(2)center dot(PMDTA) (1), Mg-4(mu-H)(6)N ''(2)center dot(PMDTA)(2) (2), Mg-5(mu-H)(7)N ''(3)center dot(PMDTA)(2) (3), Mg-2(mu-H)(2)N ''(2)center dot(DABCO)(2) (4) and Mg-2(mu-H)(2)N ''(2)center dot(I(Me)iPr)(2) (5). The PMDTA complexes 1-3 were only isolated as mixtures that could not be separated but complexes 4 and 5 have been fully characterized. The structures of the Mg hydride complexes 1, 4 and 5 are reproduced well by DFT calculations (B3PW91/6-311++G**). Bonding between Mg and hydride is largely ionic (circa 80 %) and there is very little charge transfer from the neutral donor to Mg2+. The calculated solvation enthalpies (Delta H-solv) per ligand are -12.4 kcal/mol (PMDTA), -15.9 kcal/mol (DABCO) and -20.8 kcal/mol (I(Me)iPr). In complexes 4 and 5 Bond-Critical-Points are found between the two negatively charged hydride ligands. The very high electron densities of 0.15-0.16 e/angstrom(3) in these unusual BCP's are related to the short H-center dot center dot center dot H- distances of circa 2.55 angstrom.
CRIS-Team WoS Importer:2019-10-25

Strontium Chemistry with Silicone Grease - Harder, Sjoerd; Freitag, Benjamin; Stegner, Philipp; Pahl, Jürgen; Naglav, Dominik (Zeitschrift für Anorganische und Allgemeine Chemie, 2015)
Reaction of Sr(2-Me2N–Me3Si-benzyl)(2)(THF)(2) with one equivalent of DIPP(H)N-BH-N(H)DIPP (NBN-H-2, DIPP = 2,6-iPr-phenyl) gave the strontium bora-amidinate complex Sr(NBN)(THF)(4). Traces of silicone grease, however, can change the course of the reaction completely and gave the product Sr[(DIPP)NSiMe2O]THF(4) (1) in a ca. 25% yield. Complex 1 is a S-4 symmetric cluster with a Sr4O4 core and four chelating amide side arms. From the mother liquor a second product could be isolated: the dimeric cluster [Sr(NBN-SiMe2OSiMe2O)THF](2) (2). Whereas the synthesis of complex 2 is not reproducible, complex 1 can be prepared by deliberate addition of silicone grease. Also, it was found that Sr[N(SiMe3)(2)](2), 2,6-diisopropylphenyl and cyclic hexamethyltrisiloxane can be used as the reagents. For reactions with silicone grease, a mechanism, in which silicone precoordinates the central Sr atom followed by nucleophilic Si-O bond fission is proposed.
Keywords: Amides; Strontium; Silicone

Unsupported Mg-Alkene Bonding - Thum, Katharina; Friedrich, Alexander; Pahl, Jürgen; Elsen, Holger; Langer, Jens; Harder, Sjoerd (Chemistry - A European Journal, 2020)
The first intermolecular early main group metal-alkene complexes were isolated. This was enabled by using highly Lewis acidic Mg centers in the Lewis base-free cations ((BDI)-B-Me)Mg+ and ((BDI)-B-tBu)Mg+ with B(C6F5)(4)(-) counterions ((BDI)-B-Me=CH[C(CH3)N(DIPP)](2), (BDI)-B-tBu=CH[C(tBu)N(DIPP)](2), DIPP=2,6-diisopropylphenyl). Coordination complexes with various mono- and bis-alkene ligands, typically used in transition metal chemistry, were structurally characterized for 1,3-divinyltetramethyldisiloxane, 1,5-cyclooctadiene, cyclooctene, 1,3,5-cycloheptatriene, 2,3-dimethylbuta-1,3-diene, and 2-ethyl-1-butene. In all cases, asymmetric Mg-alkene bonding with a short and a long Mg-C bond is observed. This asymmetry is most extreme for Mg-(H2C=CEt2) bonding. In bromobenzene solution, the Mg-alkene complexes are either dissociated or in a dissociation equilibrium. A DFT study and AIM analysis showed that the C=C bonds hardly change on coordination and there is very little alkene -> Mg electron transfer. The Mg-alkene bonds are mainly electrostatic and should be described as Mg2+ ion-induced dipole interactions.
CRIS-Team WoS Importer:2021-01-15